The value of reducing eutrophication in European marine areas : a Bayesian meta-analysis - Ahtiainen, Heini; Vanhatalo, Jarno (Elsevier, 2012)
One of the threats to the marine environment is eutrophication,which causes many adverse impacts that reduce human well-being. Determining the benefits of improving the state of marine areas has drawn increasing attention, especially with the establishment of the European Union Marine Strategy Framework Directive. However, existing knowledge of the benefits provided by marine ecosystem services in Europe is limited and contextspecific. This study applies meta-analysis to summarize available information on the value of reducing eutrophication in European sea areas, and to provide welfare predictions for different scenarios. The challenges related to the small number of available studies are addressed byemploying a Bayesianmeta-regression. Severalmodels are compared with prior and posterior predictive checks, and value predictions are estimated using Bayesian model averaging. The results indicate that the perceived benefits of reducing eutrophication in European marine areas can be considerable, with the predicted annual willingness to pay per person ranging from $6 for small local changes to $235 for substantial changes covering large sea areas. The findings suggest that values differ between marine regions, highlighting the importance of investigating previously unstudied geographical areas. As marine policy requires international cooperation, future studieswould also benefit fromcollaboration between countries
Keywords: Ma; rehevöityminen; merialueet; eutrophication; marine resources; marine areas; meta-analysis; benefit transfer; bayesian estimation; eutrophication